2021
DOI: 10.33746/fhj.v8i01.153
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Grade Hipertensi dengan Tingkat Kemandirian Lansia dalam Activities Of Daily Living (ADLs)

Abstract: Prevalensi hipertensi di Indonesia semakin meningkat setiap tahun terutama pada kelompok lansia. Penurunan tingkat kemandirian lansia akibat hipertensi menjadi perhatian utama dalam rangka pencapaian kualitas hidup yang optimal. Tujuan penelitian ini adalah untuk mengetahui hubungan antara derajat hipertensi pada lansia dengan tingkat kemandirian dalam menjalankan aktivitas sehari-hari. Pengambilan sampel dilakukan secara cluster sampling berjumlah 49 lansia hipertensi. Penelitian ini menggunakan pendekatan ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…This shows that the hypertension elderly at Widasari Health Center have high self-confidence, and this certainly has an impact on the adherence of the elderly in undergoing hypertension treatment. Considering that there are still 38.5% of elderly who have low efficacy, it should be improved by learning from the experiences of fellow elderly, so that their self-efficacy increases and they are obeyed in undergoing hypertension treatment (Darmawati & Kurniawan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the hypertension elderly at Widasari Health Center have high self-confidence, and this certainly has an impact on the adherence of the elderly in undergoing hypertension treatment. Considering that there are still 38.5% of elderly who have low efficacy, it should be improved by learning from the experiences of fellow elderly, so that their self-efficacy increases and they are obeyed in undergoing hypertension treatment (Darmawati & Kurniawan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ere is no more mature method to verify the framework of new economic geography. However, economists still construct some indicators and methods to measure industrial agglomeration and its economic benefits and constantly improve them [18,19]. Here, based on the industrial agglomeration measurement method, five logistics industry agglomeration measurement methods are summarized [20,21].…”
Section: Measurement Methods Of Logistics Industry Clustermentioning
confidence: 99%
“…Therefore, hypertension is not a barrier for the elderly to engage in activities independently. Darmawati and Kurniawan [25] have revealed that different hypertension stages in the elderlies indicate their different independence levels; the higher the elderlies' grade of hypertension, the lower their independence level. Therefore, families and nurses in the primary order should optimize the fulfillment of daily living activities of the elderly with hypertension.…”
Section: Impact Of Independence Level Of the Elderly On Hypertensionmentioning
confidence: 99%